2010
DOI: 10.1007/s00011-010-0301-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endogenous substance P expression on degranulation in RBL-2H3 cells

Abstract: Activated RBL-2H3 cells express endogenous SP which plays a role in antigen-induced degranulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In line with this, Berger et al 38 found a coregulated decrease of TAC4 mRNA and TACR1 (that encode TK receptor 1) mRNA as well as their proteins in monocytes and macrophages following the activation by monocytic differentiation cytokines. It is also noteworthy that SP has been shown to be increased in activated mass cells, and knocking down of endogenous SP reduced the degranulation ability of the cells 39 . These results clearly support the role of TKs, especially HK‐1 and SP, in different stages of immunomodulatory processes, which can assist in developing more‐effective therapeutic approaches by introducing these new targets to treat immune disorders.…”
Section: Immune Cell Development and Functionssupporting
confidence: 58%
“…In line with this, Berger et al 38 found a coregulated decrease of TAC4 mRNA and TACR1 (that encode TK receptor 1) mRNA as well as their proteins in monocytes and macrophages following the activation by monocytic differentiation cytokines. It is also noteworthy that SP has been shown to be increased in activated mass cells, and knocking down of endogenous SP reduced the degranulation ability of the cells 39 . These results clearly support the role of TKs, especially HK‐1 and SP, in different stages of immunomodulatory processes, which can assist in developing more‐effective therapeutic approaches by introducing these new targets to treat immune disorders.…”
Section: Immune Cell Development and Functionssupporting
confidence: 58%
“…Similarly, we also observed the upregulation of SP levels in synovial tissues obtained from patients with different stages of DDH compared with those obtained from the control group. It has been reported that SP is involved in the mediation of inflammatory hyperalgesia and immune regulation [ 40 ]. In this study, we explored the possible correlation between SP and inflammatory cytokines in the SF of patients with severe DDH.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that the expression of endogenous SP mRNA and peptide is significantly increased under IgE-activated conditions and that small hairpin RNA (shRNA)- mediated knockdown of endogenous SP can reduce the ability of IgE-activated mast cells to undergo degranulation. 240 This finding suggests that endogenous SP plays an important role in mast cell antigen-mediated degranulation and thus enhances the progression of allergic inflammation. 240 Indeed, it is notable that SP is expressed not only by neurons, but also in immune cells such as mast cells 240 which release allergic mediators such as histamine, 241 thereby exacerbating allergic symptoms.…”
Section: Mechanismsmentioning
confidence: 98%
“… 240 This finding suggests that endogenous SP plays an important role in mast cell antigen-mediated degranulation and thus enhances the progression of allergic inflammation. 240 Indeed, it is notable that SP is expressed not only by neurons, but also in immune cells such as mast cells 240 which release allergic mediators such as histamine, 241 thereby exacerbating allergic symptoms. It is possible that widespread expression of SP in diverse cell types may indicate a multifunctional role for SP in a wide variety of physiologic and pathophysiologic conditions by activating a multitude of signalling pathways.…”
Section: Mechanismsmentioning
confidence: 98%